Enhancing Soybean (Glycine max L. Merrill.) Productivity through Varied Phosphorus Levels and Foliar Application of Nano-DAP - Shivu , H. K.; Somanagouda, G.; Salakinkop, S. R.; Roopa, U.; Rathod, Nagesh; Channakeshva, R. (International Journal of Bio-resource and Stress Management, 2026)
A field experiment was conducted at AICRP on soybean, MARS, UAS, Dharwad, Karnataka during kharif, 2023 (July to October) to study the response of soybean through varied phosphorus levels and foliar application of Nano-DAP. The experiment was replicated thrice in a split-plot design with three main plots and four subplots. Application of 100% recommended dosage of phosphorus. recorded significantly higher plant height (42.15 cm), number of branches plant-1 (6.73), leaf area (12.23 dm2 plant-1), leaf area index (4.07), total dry matter accumulation/plant (28.78 g), SPAD value (50.10), number of nodules (47.08 plant-1), number of pods (45.26 plant-1), seed yield plant-1 (15.88 g), 100 seed weight (15.20 g), seed yield (2564 kg ha-1), haulm yield (3222 kg ha-1), net returns (` 84,517 ha-1) and B-C ratio (2.94) over 75% recommended dosage of phosphorus and control. Among foliar nutrition, foliar application of Nano-DAP @ 4 ml l-1 at 30 and 45 DAS recorded significantly higher plant height (39.77 cm), number of branches plant-1 (6.34), leaf area (11.20 dm2 plan-1), leaf area index (3.75), total dry matter accumulation plant-1 (26.27 g), SPAD value (47.92), number of nodules (40.60 plant-1), number of pods plant-1 (41.86), seed yield plant-1 (14.55 g), 100 seed weight (14.74 g), seed yield (2330 kg ha-1), haulm yield (2922 kg ha-1), net returns (` 71,513 ha-1) and B-C ratio (2.59) over no foliar applications. Among the interaction effects, application of 100% RDP+foliar application of Nano-DAP @ 4 ml l-1 at 30 and 45 DAS (M1S3) recorded significantly higher productivity, quality parameters and economic returns of soybean crop.